2022
DOI: 10.1002/cre2.621
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical findings of temporomandibular joint with serological results in rheumatoid arthritis patients

Abstract: Objectives This study aimed to determine the frequency of temporomandibular joint (TMJ) involvement in patients with rheumatoid arthritis (RA) and to find out the correlation of serological tests with clinical symptoms of TMJs in RA patients. Patients and Methods This cross‐sectional study was performed on 40 patients with RA classified into two groups according to their duration of the disease. Clinical examination as well as laboratory tests were done for participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our study investigates the appearance of signs and symptoms of TMD in patients with newly diagnosed rheumatic disease, prior to the initiation of any treatment. This contrasts with previous research that typically assesses TMD prevalence in patients already receiving antirheumatic treatment or hospitalized for their condition [13,14]. This distinction is crucial, as treatment may influence the presentation and severity of TMD symptoms, potentially masking their true prevalence and characteristics in untreated patients [15].…”
Section: Discussionmentioning
confidence: 83%
“…Our study investigates the appearance of signs and symptoms of TMD in patients with newly diagnosed rheumatic disease, prior to the initiation of any treatment. This contrasts with previous research that typically assesses TMD prevalence in patients already receiving antirheumatic treatment or hospitalized for their condition [13,14]. This distinction is crucial, as treatment may influence the presentation and severity of TMD symptoms, potentially masking their true prevalence and characteristics in untreated patients [15].…”
Section: Discussionmentioning
confidence: 83%
“…thus, the pathological process of developing Ra may be more pronounced in the subjects of Kroese et al [26]. in subjects with diagnosed Ra, previous studies report that elevated levels of RF and accP are related to more frequent clinical signs and symptoms of tMD compared to controls [20,32,35].…”
Section: Discussionmentioning
confidence: 91%
“…Yet, large range of frequencies have been reported due to differences in study design and diagnostic criteria (for example lin et al [19]). also, Jalal et al [35] reported an increasing frequency of tMD signs with regard to the time of diagnosing the Ra: 15% of subjects with Ra diagnosed within 5 years had tMD signs compared to 40% of subjects with Ra diagnosed within 6-10 years. this implies that majority of subjects with Ra have some signs of tMD and those who could benefit from further tMD examination and management should be identified and directed to a suitable dental clinic.…”
Section: Discussionmentioning
confidence: 92%
“…Our study investigates the unseen emergence of TMD signs and symptoms in newly diagnosed rheumatic patients before any treatment commences. Prior studies on TMD prevalence in rheumatic patients often involve individuals already receiving treatment or in hospital settings and not newly diagnosed, untreated patients [18,19]. The time elapsed between initial rheumatic disease diagnosis and recording TMD could affect the differentiation and severity of TMD symptoms, potentially obscuring the genuine prevalence in untreated patients [20].…”
Section: Discussionmentioning
confidence: 99%